1997
DOI: 10.1111/j.2042-7158.1997.tb06099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan on Renal Function in Patients with Chronic Renal Failure

Abstract: The effects of chitosan have been investigated on eighty patients with renal failure undergoing long-term stable haemodialysis treatment. The patients were tested after a control treatment period of 1 week. Half were fed 30 chitosan tablets (45 mg chitosan/tablet) three times a day. Ingestion of chitosan effectively reduced total serum cholesterol levels (from 10.14 +/- 4.40 to 5.82 +/- 2.19 mM) and increased serum haemoglobin levels (from 58.2 +/- 12.1 to 68 +/- 9.0 g L-1). Significant reductions in urea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 5 publications
2
32
0
1
Order By: Relevance
“…14,15 The deacetylation of chitin to form chitosan increases the positive charge density on the molecule, permitting it to form these bonds. 14 Studies in rats, 16,17 and in humans 11,12 suggest that dietary chitosan increases bile acid excretion and decreases plasma cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The deacetylation of chitin to form chitosan increases the positive charge density on the molecule, permitting it to form these bonds. 14 Studies in rats, 16,17 and in humans 11,12 suggest that dietary chitosan increases bile acid excretion and decreases plasma cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…We then looked at published studies in humans, where a significant drop in blood cholesterol was observed with chitosan use at effective doses ranging from 1.35 to 3.0 g daily. 11,12 This suggested to us that an effective dose, if one existed, might be at the high end of the intake suggested by the manufacturer and the distributor. Therefore, we instructed subjects to take a total of 15 capsules daily (5.25 g chitosan=day).…”
Section: Methodsmentioning
confidence: 99%
“…In a study involving 40 patients with renal failure undergoing haemodialysis treatment, administration of chitosan (1350 mg, twice a day), resulted in the reduction in total serum cholesterol levels (10.4p4.4 to 5.82p2.19 m) with an increase in serum haemoglobin levels (58.2p12.1 to 68.0p9.0 g L − 1 ), but a significant reduction in urea and creatinine levels in serum were observed after 4 weeks of chitosan administration (Jing et al 1997), suggesting the potential application of the polymer in treating patients with renal failure. Okamoto et al (1995) analysed the accelerating effects of open wound healing by chitin and chitosan in dogs.…”
Section: Renal Effectsmentioning
confidence: 99%
“…For example, due to its cicatrizant properties it has been used as a component in all types of dressing, surgical sutures, dental implants and in rebuilding bones and gums [15]. Chitosan is also helpful in kidney failure as it binds with toxins in the digestive tract thereby leading to their excretion [11].…”
Section: Ultra-pure Grade For Biopharmaceutical Usesmentioning
confidence: 99%